The Physical Education in Child Education: the figure of the specialist in the Child Education of Vitoria. - Alexandre Freitas Marchiori; Fernanda Freitas Rezende Rodrigues; Rosemary Coelho de Oliveira (Universidade Federal de Santa Catarina, 2009)
This article aims to share a thread that permeates the teaching in Physical Education in the Centros Municipais de Educação Infantil (CMEI) council of Vitoria. It is a theoretical and practical issues related to curriculum, the role of specialist in the education system, its characteristics and working conditions that are placed by management sectors as much local, as national. It is that professionals have contributed to a quality education and committed to the principles and rights of students, recognized as subjects / actors in the teaching-learning process. The question "What Physical Education in Child Education?" Urged the authors to discuss in depth the teaching in CMEIs do and bring some thoughts that have guided interventions in the area of Physical Education. Having shared some questions, try to talk to authors and official documents to understand the continuous movement to "rethink the practice" every day, always looking to meet children from zero to six in their needs, is divided between the intervention and care educate. Another point is the Culture / Arts to take over the company's history, where children have the right to access, the knowledge about the experience of the content addressed in the daily activities of CMEIs. And it must also produce knowledge and contribute to the multiple languages that permeate the development in the age group zero to six years. Keywords: Physical Education, Child Education, Specialist, Languages.